Hydrological Conditions Affect the Interspecific Interaction between Two Emergent Wetland Species - Zhou, Jian; Zheng, Li-Di; Pan, Xu; Li, Wei; Kang, Xiao-Ming; Li, Jing; Ning, Yu; Zhang, Ming-Xiang; Cui, Li-Juan (Frontiers in Plant Science, 2018)
Hydrological conditions determine the distribution of plant species in wetlands, where conditions such as water depth and hydrological fluctuations are expected to affect the interspecific interactions among emergent wetland species. To test such effects, we conducted a greenhouse experiment with three treatment categories, interspecific interaction (mixed culture or monoculture), water depth (10 or 30 cm depth) and hydrological fluctuation (static or fluctuating water level), and two common emergent wetland plant species, Scirpus planiculumis Fr. (Cyperaceae) and Phragmites australis var. baiyangdiansis (Gramineae). An increase in the water depth significantly restrained the growth of both S. planiculumis and P. australis, while hydrological fluctuations did not obviously alter the growth of either species. In addition, both water depth and hydrological fluctuations significantly affected the interspecific interaction between these two wetland species. P. australis benefited from interspecific interaction under increasing water depth and hydrological fluctuations, and the RII values were clearly positive for plants grown at a water depth that fluctuated around 30 cm. The results may have some implications for understanding how S. planiculumis and P. australis, as well as wetland communities, respond to the natural variation or human modification of hydrological conditions.